A Suggestion for an Effective Use of a Computer-aided Diagnosis System in Screening for Hyperthyroidism - Alpérovitch, A.; Fragu, P. (Methods of Information in Medicine, 1977)
A computer-assisted program for diagnosing hyperthyroidism, specially devoted to the screening of functional thyroid status, has been written using data provided by 359 patients, 282 euthyroid and 77 hyperthyroid. The model is based on Bayes’ theorem.Using only 9 clinical signs and the free thyroxin index, the program achieved, on a test-sample of 117 new patients, an overall accuracy of 90% ; 10% of the cases were in the zone of uncertainty, and none was misdiagnosed.Different screening strategies are examined and their results discussed.
Keywords: Computer-aided Decision; Thyroid; Screening; Signs Interactions